Methods of Terrorism Financing: Criminal procedural obstacles to the prevention of crime in Germany, Liechtenstein, Austria and Switzerland - Teichmann, Fabian (Internationales und Europäisches Strafverfahrensrecht, 2021)
I. Bibliography – II. Internet sources – III. List of abbreviations and acronyms – 1. Introduction – 2. The state of research and research gaps – 3. Empirical investigation – 4. Discussion of the empirical results – 5. Criminal procedural implications of the empirical study – 6. Summary – 7. Appendix – Appendix 1: Memory transcripts of the informal interviews – Appendix 2: Generalizations of the formal interviews – Appendix 3: Document citations – Appendix 4: Interview Guide – Appendix 5: Preliminary Publications